Bariery zastosowania faktoringu jako obcego źródła finansowania działalności przedsiębiorstw - Czarecki, Jacek (Obstacles for Using Factoring as an External Source of Financing Company, 2007)
Nowadays companies can use various sources of financing their companies' operations. One of them is factoring. This instrument is becoming more and more popular in Poland, however, despite this fact, the turnover of the factoring branch is still relatively low compared to the corresponding turnover volumes in other countries. This article is an attempt to discover reasons for this state of affairs. The discussion on obstacles for using factoring by companies concentrates on three major groups of barriers limiting the frequency of employing this source of financing, namely, the costs of factoring, the risk level for the factor and the administrative aspects of its usage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 106-114